English learning motivation of young learners in Danish primary schools - Fenyvesi, Katalin (Language teaching research : LTR, 2020)
This study has investigated, in a quantitative survey, how the attitudes toward English lessons and the motivation for learning English as a foreign language (EFL) of 276 Danish EFL learners (starting age 7 and 9 years) changed within one year. Second, a subsample of children were interviewed. The study investigated what they liked and disliked about English lessons, and what motivated them to learn English. The results have shown that children’s positive attitudes toward their English lessons decreased significantly during the time of the study. More boys than girls described English as their favorite subject, and children enjoyed real-life situations, variation and differentiation in the English lessons. Children were strongly motivated by English being an international language, their reliance on significant others as motivators for FL learning decreased significantly with time, and high achievers, as opposed to low achievers, were motivated by engaging in gaming and watching YouTube videos in English. Pedagogical implications are discussed.